It is all about clauses: Speech analysis using systemic functional linguistics theory - Darong, Hieronimus Canggung (Universitas Islam Negeri Banda Aceh, 2022)
Text and context are tightly related. Although previous studies have revealed the benefits of employing Systemic Functional Linguistics theory (SFL) in revealing the language functions, the specific examination of text ideational or experiential focusing on transitivty process type analysis is lacking. Therefore, the aim of this study is to examine the transitivity process type of a text. To achieve this purpose, Joe Biden’s victory speech was chosen and analyzed. In this respect, to make the analysis easily done, the speech text was changed into some sentences and clauses and thereafter analyzed following the aim of the study in question. The result of analysis has shown that the the material process type appears at most, which indicates the action of the participants involved in the speech. In addition, by means of transitivity analysis, interpersonal and power relation might be revealed as the existence of pronouns linking to verbs used in clauses of the text. As a conclusion, different language patterns might signify different concerns of the experintial or ideational functional category. Future research studies, by means of different ways of analysis, might be of benefit to examine the effectiveness of Systemic Functional Linguistics theory (SFL) in a text analysis.